The Impact of Joint Auditing on Audit Costs A field study on a sample of external audit offices - adel khalil, abdelrahmanne (Journal of Research in Finance and Accounting, 2022)
This study aimed to identify the impact of joint auditing on audit costs, (fixed, variable, conditional). The study found that the joint audit increased the audit costs, and the formation of a joint audit team consisting of a large number of members with high professional experience contributed in increasing audit costs. The study recommended paying attention to adjusting the number of members of the joint audit team as needed to reduce audit costs.